Mediating effect of perceived destination image between K-dramas' motivational influence and visit intention to South Korea / Felipe B.Pablo IV, Joy DC. David and Patricia S. Ambrosio - IV, Felipe B.Pablo; David, Joy DC; Ambrosio, Patricia S. (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
One of the central points of Hallyu, or Korean Wave, is Korean drama (K-drama) which has been popular in the Philippines since early 2000's. This study aims to explore K-dramas influence on Filipino young adult viewers' intention to visit South Korea by testing the relationships among K-dramas' motivational influence, and perceived destination image and visit intention to South Korea. Data were gathered from 181 younger adults through a survey done online. Utilizing partial least squares structural equation modelling (PLS-SEM), results imply that K-dramas' motivational influence significantly affect destination image and intention to visit South Korea, and destination image significantly influences visit intention to the country. Perceived destination image also mediates the influence of K-dramas' on intention to visit the South Korea. The study contributes to the study on presence of Hallyu in the Philippines. Results has implications to national and local tourism organizations, and film and media suites in the Philippines to understand effects of media outputs on tourist behavior. The study contributes to the dearth in literature discussing the relationships among film and television effects, destination image, and visit intention, and the mediating role of perceived image.